Enzymatic characteristics of immobilized carbonic anhydrase and its applications in CO2 conversion - Ren, Sizhu; Chen, Ruixue; Wu, Zhangfei; Su, Shan; Hou, Jiaxi; Yuan, Yanlin (Colloids and surfaces, B, Biointerfaces, 2021)
[Display omitted] •The enzymatic characteristics of immobilized CA are comprehensively summarized.•Approaches for immobilization and the advantages and disadvantages are discussed.•Applications of CA in native and immobilized status are reviewed.•Studies of CO2 conversion are summarized, providing ideas for CO2 utilization. Native carbonic anhydrase (CA) has been widely used in several different applications due to its catalytic function in the interconversion of carbon dioxide (CO2) and carbonic acid. However, subject to its stability and recyclability, native CA often deactivates when in harsh environments, which restricts its applications in the commercial market. Maintaining the stability and high catalytic activity of CA is challenging. Immobilization provides an effective route that can improve enzymatic stability. Through the interaction of covalent bonds and van der Waals forces, water-soluble CA can be combined with various insoluble supports to form water-insoluble immobilized CA so that CA stability and utilization can be greatly improved. However, if the immobilization method or immobilization condition is not suitable, it often leads to a decrease in CA activity, reducing the application effects on CO2 conversion. In this review, we discuss existing immobilization methods and applications of immobilized CA in the environmental field, such as the mineralization of carbon dioxide and multienzyme cascade catalysis based on CA. Additionally, prospects in current development are outlined. Because of the many outstanding and superior properties after immobilization, CA is likely to be used in a wide variety of scientific and technical areas in the future.